2010
DOI: 10.1371/journal.pone.0010901
|View full text |Cite
|
Sign up to set email alerts
|

Prepatterning in the Stem Cell Compartment

Abstract: The mechanism by which an apparently uniform population of cells can generate a heterogeneous population of differentiated derivatives is a fundamental aspect of pluripotent and multipotent stem cell behaviour. One possibility is that the environment and the differentiation cues to which the cells are exposed are not uniform. An alternative, but not mutually exclusive possibility is that the observed heterogeneity arises from the stem cells themselves through the existence of different interconvertible substat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 44 publications
(53 reference statements)
0
15
0
Order By: Relevance
“…The HA-STELLA DNA fragment was gel-purified using a DNA extraction kit from Fermentas. The Tomato encoding gene of pCAG-Tomato-IRES-puromycin [38] was excised using XhoI and NotI , and was replaced by the HA-STELLA DNA fragment. The plasmid pCAG-HA-STELLA-IRES-puromycin was then transfected into either H7 or Shef3 to establish the STELLA over-expressing cell lines using electroporation.…”
Section: Methodsmentioning
confidence: 99%
“…The HA-STELLA DNA fragment was gel-purified using a DNA extraction kit from Fermentas. The Tomato encoding gene of pCAG-Tomato-IRES-puromycin [38] was excised using XhoI and NotI , and was replaced by the HA-STELLA DNA fragment. The plasmid pCAG-HA-STELLA-IRES-puromycin was then transfected into either H7 or Shef3 to establish the STELLA over-expressing cell lines using electroporation.…”
Section: Methodsmentioning
confidence: 99%
“…The possibility then exists that these substates might be differently biased towards particular fates, as we recently found in the EC cell line, NTERA2. Although these pluripotent stem cells are seemingly homogeneous, they nevertheless appear to exist in interconvertible pro‐neural and pro‐non‐neural substates which tend towards neural and non‐neural fates upon induction with retinoic acid (RA) (Tonge et al. , 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Draper et al and Tonge et al have indicated that expression of proteins associated with pluripotency fluctuate within the heterogeneous stem cell population, but pluripotency is maintained as long as the expression remains above an unknown threshold. [18][19][20] In the past several years, studies have demonstrated that subpopulations exist within the pluripotent state. Laslett and coworkers were the first to suggest that subpopulations exist within the hESC population and represent different states of lineage commitment by demonstrating the concurrent expression of genes associated with pluripotency and lineage transcription factors.…”
Section: Figmentioning
confidence: 99%